Recent development on heterogeneous catalysts for syngas production via co2 utilization - M. A., A. Aziz; Herma Dina, Setiabudi; L. P., Teh; N. H., R. Annuar; S., Triwahyono; A., A. Jalil (Universiti Malaysia Pahang, 2018)
In the past decade, the excessive use of fossil fuels by rapid industrial development has brought several environmental problems such as the rising of global warming gases concentration, including carbon dioxide (CO2), in atmosphere. CO2 has become the focus of attention because of the position of CO2 as the primary greenhouse gas and the implication of its emissions on the problem of climate change. Recently, the concept the CO2 utilization to chemicals and energy products is promising due to the high potential market and promising benefits. One of the significant process in CO2 utilization is dry reforming, where CO2 is used for the catalytic reforming of hydrocarbons for the production of synthesis gases (syngas - hydrogen and carbon monoxide). Current research is focused on the dry reforming of alkane (methane, ethane, butane) [1,2] and alcohol (ethanol, methanol and glycerol) [3–5]. In recent years, syngas production from dry reforming of hydrocarbon via heterogeneous catalysts has recently attracted a considerable amount of attention, as demonstrated by the burgeoning number of publications (see Figure 1).